THE EFFECTS OF CORPORATE SOCIAL RESPONSIBILITY (CSR), ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG), AND COMPANY SIZE ON TAX AVOIDANCE (A Study of Manufacturing Companies Listed on the BEI from 2019 to 2023) - Nabilah Anisah Putri Hasbi (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
Taxes serve as the primary source of government revenue and are utilized to finance various public programs aimed at improving societal welfare. However, companies, as taxpayers, often perceive taxes as a financial burden that reduces profitability, thereby encouraging the practice of tax avoidance. This study aims to examine the effects of Corporate Social Responsibility (CSR), Environmental, Social, and Governance (ESG), and Company Size on Tax Avoidance among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This study employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample was selected through purposive sampling, resulting in 52 manufacturing companies with a total of 260 firm-year observations. Data were analyzed using multiple linear regression with SPSS version 25. The findings indicate that ESG and Company Size have a significant effect on Tax Avoidance, whereas Corporate Social Responsibility (CSR) does not have a significant effect on Tax Avoidance.